An Investigation into the Effectiveness of Collaborative Brainstorming at the Pre-writing stage in Intermediate English Classes at a University in Hanoi = Khảo sát hiệu quả của việc thảo luận ý tưởng theo nhóm trước khi viết trong lớp học tiếng Anh trình - Trần, Thị Ánh Tuyết (University of Languages and International Studies, 2017)
Brainstorming has been a popular technique organized individuallyor collaboratively for idea generation in many fields. While a number of studies have been reported on the productivity of group idea generation, the effectiveness of collaborative brainstorming for generating ideas as pre-writing techniques have not received deep concern. This thesis reports on a qualitative action study that emerged from reflective teaching practice in an intermediate English class. The research investigated the effectiveness of collaborative brainstorming training on students’ idea performance in writing papers and on students’ learning of writing skills through in-depth interviews, observations, students’ writing papers and students’ journals. The study indicates that collaborative brainstorming training with additional rules can significantlyimprove quantity and quality of ideas in paragraph writing, but not in letter writing. Besides, training has had positive effects on students’ learning of writing skills. The findings of the study, therefore, make important contributions to the implementation of collaborative brainstorming in the English language teaching practice